-2+16g+9=-13+17g

Simple and best practice solution for -2+16g+9=-13+17g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2+16g+9=-13+17g equation:



-2+16g+9=-13+17g
We move all terms to the left:
-2+16g+9-(-13+17g)=0
We add all the numbers together, and all the variables
16g-(17g-13)-2+9=0
We add all the numbers together, and all the variables
16g-(17g-13)+7=0
We get rid of parentheses
16g-17g+13+7=0
We add all the numbers together, and all the variables
-1g+20=0
We move all terms containing g to the left, all other terms to the right
-g=-20
g=-20/-1
g=+20

See similar equations:

| 10b+19=-9+14b | | 0.75(x+20)=2+0.5(x+2) | | 4.9q+18.76=7.2q-3.1q+9.56 | | -8x+(7x)=16 | | y=-1,1 | | 15-2z=-z | | 0.5(x+8)76=0.25(x+46) | | 11s=-11+10s | | 7/12x=7/4 | | 3x-(2x+4)=4x-19 | | -9.7w-3.26=9.97-7w | | 7x-4(3x+5)=10(x-15)-5 | | -1+12m=-15+13m | | 18-2n=2 | | 19t+18=-12+3t+18t | | 20-16-15d=-20-12d | | A=3^x+1.3^x-2/3^x-1.3^x-2 | | -8-8v=10-5v+9 | | -9k-4=-18-7k | | -10+8n=10n+10 | | -3s-7s+9=-9-7s | | Y=5x^2+15x+4 | | 5m+10=4m | | -5q+6=-8q | | 2u-10=10+4u | | -7d=-6d-10 | | 7s=8-s | | -g=6-2g | | 100+20m=51/4 | | 6(g+17)=6(g)+6(17) | | 49x2=9 | | 2*1+4y=6 |

Equations solver categories